2020
DOI: 10.3390/ani10091465
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Ration Negative in Dietary Cation–Anion Difference and Varying Calcium Supply Fed before Calving on Colostrum Quality of the Dams and Health Status and Growth Performance of the Calves

Abstract: This study investigated the effect of diets negative in dietary cation–anion difference (DCAD) or restricted in Ca fed prepartum to dairy cows for three weeks on colostrum yield and composition, and the health and growth performance of their calves. Thirty-six pregnant non-lactating Holstein-Friesian cows were randomly assigned to three isoenergetic diets: (1) low Ca: 0.24% Ca, DCAD: +86 mEq/kg; (2) high Ca: 1.23% Ca, DCAD: +95 mEq/kg; and (3) low DCAD: 1.28% Ca, DCAD: −115 mEq/kg (all dry matter (DM) basis). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 51 publications
(100 reference statements)
2
9
0
Order By: Relevance
“…Treatment did not affect BW of calves at birth. The same lack of effect of prepartum DCAD on birth BW has been previously shown in cows fed different levels of negative DCAD (Collazos et al, 2017;Diehl et al, 2018) or when comparing positive with negative DCAD (Weich et al, 2013;Rajaeerad et al, 2020). Dams in all 3 treatments received the prepartum diet for a mean of 22 d, and treatment did not affect intake of milk or starter grain DM, nor growth performance of calves in the preweaning period.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Treatment did not affect BW of calves at birth. The same lack of effect of prepartum DCAD on birth BW has been previously shown in cows fed different levels of negative DCAD (Collazos et al, 2017;Diehl et al, 2018) or when comparing positive with negative DCAD (Weich et al, 2013;Rajaeerad et al, 2020). Dams in all 3 treatments received the prepartum diet for a mean of 22 d, and treatment did not affect intake of milk or starter grain DM, nor growth performance of calves in the preweaning period.…”
Section: Discussionsupporting
confidence: 67%
“…Both nutrient intake and morbidity affect growth in calves, and the fact that treatment had no effect in either explains the lack of differences in daily BW gain and final BW of calves on d 56. Rajaeerad et al (2020) showed that feeding an acidogenic diet prepartum did not affect daily BW or feed conversion ratio in calves in the first 70 d of life; however, calves born to dams fed the acidogenic compared with the alkalogenic diet had lower mean BW in the first 55 d because of differences in wk 1 and 2 after birth. After weaning on d 55 of age, BW on d 70 did not differ between calves born to dams fed the acidogenic or the alkalogenic diet (Rajaeerad et al, 2020).…”
Section: Discussionmentioning
confidence: 96%
“…Meanwhile, Svensson and Liberg (2006) demonstrated that dam parity was not associated with the BRD incidence rate in calves [20]. Birth weight is reported to be affected by other factors, including dam management during the dry period and genetic predisposition [29,31,34]. The influence of other factors on birth weight may have masked the effect of dam parity on BRD risk.…”
Section: Discussionmentioning
confidence: 99%
“…Such discordance might be explained by the differences in the climate in these study areas. In Ontario, Minnesota, and Tokachi, harsh winters, cold stress, and poor ventilation within the calf barns could be significant risk factors for the incidence of BRD [ 34 ]. In contrast, temperate weather in summer prompted open calf barns, which provided good ventilation with less cold stress and decreased the risk of BRD.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the effects of feeding negative-DCAD diets for an extensive time prior to calving have minimal negative effects on the cow [83,84]. However, one recent study showed that calves born to cows fed a negative-DCAD diet had a lower BW and an average daily weight gain than calves from cows fed positive-DCAD diets [85]. We are not aware of any published research investigating the feeding of negative-DCAD diets on the sow farrowing duration and the stillbirth rate.…”
Section: Sow-specific Dietsmentioning
confidence: 99%